Amperometric Biosensor Detecting Dopamine Based on Polypyrrole/Reduced Graphene Oxide/Nickel Oxide/Glassy Carbon Electrode - Shindy Ayu Netania Priyanto; Elly Septia Yulianti; Ahmad Zakiyuddin; Siti Fauziyah Rahman (Journal of Electrical and Computer Engineering)
Dopamine (3,4-dihydroxyphenethylamine) (DA) plays an important role in influencing emotions, pleasure sensations, concentration, pain, and coordination of body movements. However, abnormal levels of DA in the brain can lead to Parkinson’s, Alzheimer’s, or schizophrenia diseases. A biosensor is defined as an analytical tool that combines certain biological recognition components with a physical transducer. A comprehensive study was conducted to enhance the performance of DA detection by incorporating reduced graphene oxide (rGO), polypyrrole (PPy), and nickel oxide (NiO) into the glassy carbon electrode (GCE). DA levels were measured using cyclic voltammetry (CV) with a three-electrode configuration. Material characterization was evaluated by scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR). The results obtained indicate that PPy/rGO/NiO/GCE has a detection limit of 0.195 mM and a sensitivity of 25.887 A mM−1 cm−2 for a linear range of 0.01–1 mM.